Distribution of 10-year cardiovascular disease risk levels in Mongolia: results from nation-wide health screening program - Bayarbold Dangaa; Batzorig Bayartsogt; Ariuntuya Tuvdendorj; Enkhbold Sereejav; Khurelbaatar Nyamdavaa; Damdindorj Boldbaatar; Enkhtur Yadamsuren; Otgonbat Altangerel; Oyuntugs Byambasukh; Narantuya Davaakhuu; Tumur-Ochir Tsedev-Ochir; Mijidsuren Ganbat; et al. (Frontiers in Public Health)
IntroductionThe Mongolian government recently initiated the first nationwide health screening program to assess the health status of the entire population using age-group specific health risk assessments related to the major noncommunicable diseases and behavioral risk factors. Based on data collected from nationwide health screening program, we estimated the distribution of 10-year cardiovascular disease (CVD) risks in the general population by using the risk prediction model recently published by the World Health Organization (WHO).MethodsA representative sample of 35,769 adults aged between 40 and 80 years old participated in nationwide health screening program, which covered all 21 Mongolian provinces and 9 districts in the capital city Ulaanbaatar. Data used in the present study were obtained from the first wave of the screening program, which was held throughout Mongolia between May 2022 and February 2023. To assess the four categories of CVD risk and determine the 10-year risk of a fatal/non-fatal event, we used the WHO CVD risk 2019 laboratory-based cardiovascular disease risk charts. The following key risk factors were used to assess the 10-year CVD risk: gender, age, location, smoking status, body mass index, total cholesterol level, history of diabetes, fasting glucose level, and blood pressure level. The 10-year risk for CVD was divided into four groups: low risk (< 10%), mild risk (10 to 20%), moderate risk (20 to 30%), and high risk (> 30%).ResultsTotal of 35,769 adults aged between 40 and 80 years old participated in the nationwide health screening program. The mean age of the participants in the screening program was 54.4 ± 9.3 years. According to the CVD charts published by the WHO, about 48% (n = 17,282) of the study population had a low 10-year CVD risk (<10%), 41% (n = 14,554) had a mild risk (10–20%), 12% (n = 3,502) had a moderate risk (20–30%), and 1% (n = 431) had a high risk (>30%).ConclusionMore than half of the screening program participants were identified as having a 10-year CVD risk greater than 10%. Effective intervention focusing on the male population living in urban areas, and target on major risk factors like hypertension, smoking and diabetes can be strategic approach to reducing the CVD risk in Mongolia.